GEN-10 WHOLE GENOME LANDSCAPE OF GLIOBLASTOMA, IDH-WILD TYPE. (3rd December 2022) - Nakashima, Takuma; Funakoshi, Yusuke; Uneda, Atsuhito; Nambu, Shohei; Tanaka, Shota; Ishida, Joji; Saito, Ryuta; Hanaya, Ryosuke; Yoshimoto, Koji; Narita, Yoshitaka; Suzuki, Hiromichi
Abstract: Introduction: Glioblastoma, IDH-wild type (GBM) is the most common malignant brain tumor with a dismal prognosis. Although its coding region is well-analyzed, little is yet known about the landscape of whole-genome in GBM. Here, we analyzed whole-genome sequencing data from large cohorts to completely uncover the genetic aberrations in GBM. Methods: We analyzed 281 whole-genome sequencing data of patients with GBM, of which 152 cases are from our cohort with deep coverage (×120) and 129 cases are from a public database. Results: The median numbers of somatic mutations and structural variants (SVs) per case are 3.0/Mb and 62.5, respectively. While a complex SV is rare in other malignant brain tumors such as IDH-mutant glioma (35% of samples), a large proportion of GBM cases (85%) have complex SV with ≥10 breakpoints. CDKN2A/B homozygous deletions (HDs) are usually comprised of a simple deletion in IDH-mutant glioma whereas about a quarter of CDKN2A/B HDs in GBM are induced by complex SVs. In addition, 30.5% of extrachromosomal DNA (ecDNA) involves multiple chromosomes. Taken together, complex SVs could play a key role in the initiation and progression of GBM. Our deep WGS enables us to delineate a fine view of clonal architecture, where mutational signature varies between clonal and subclonal mutations. The majority of clonal mutations consist of the clock-like signature, whereas subclonal mutations have a relatively low proportion of the clock-like signature. Instead, several other signatures including the APOBEC signature significantly increase in subclones, presuming that various mutational processes along with the clock-like signature contribute to the GBM pathogenesis in its progression phase. Conclusions: GBM evolves through exploiting complex structural variants involving multiple driver genes and the accumulation of genetic mutations caused by distinct mechanisms depending on its developmental stage.